Geohazard assessment along the road alignment using remote sensing and GIS: Case study of Taplejung-Olangchunggola-Nangma road section, Taplejung district, east Nepal (Journal of Nepal Geological Society, 2014)
Landslides and roadside slope failures resulting in road blockage, damage and economic losses are regular phenomena in the mountain regions of Nepal. Road construction in the northern belt of Himalaya is a challenging task, mainly due to the anticipated geo hazard in the region and remoteness of the area. The situation is often intensified in the region due to limited engineering geological and geotechnical information. The geo disaster risk further increases due to road construction. Geo hazard assessment is prerequisite to have best road alignment in mountain areas that are basically landslide-prone in many cases. The products of space science (like satellite imageries) could be a better choice for this purpose because of availability of high resolution imageries and their ready availability. The data acquired from space borne technology can be used to better assess the geological hazard condition along the road alignment. The present paper focuses to this aspect with the case study of a road section of Taplejung-Olangchunggola- Nangma, reaching the Nepal-Tibet border. The geo hazard assessment along the road corridor has been carried out through extracting the relevant information from satellite images in addition to the use of available secondary information as well as field study. A GIS database has been developed with the required information, which was used to prepare various thematic layers (like geology, drainage density, slope, aspect, rainfall), followed by further analysis. The suitability of the existing alignment has been evaluated with respect to the geo hazard condition along the road alignment.